Production of Monodisperse Oil-in-Water Droplets and Polymeric Microspheres Below 20 μm Using a PDMS-Based Step Emulsification Device - Naotomo Tottori; Seungman Choi; Takasi Nisisako (Micromachines, 2025)
Step emulsification (SE) is renowned for its robustness in generating monodisperse emulsion droplets at arrayed nozzles. However, few studies have explored poly(dimethylsiloxane) (PDMS)-based SE devices for producing monodisperse oil-in-water (O/W) droplets and polymeric microspheres with diameters below 20 µm—materials with broad applicability. In this study, we present a PDMS-based microfluidic SE device designed to achieve this goal. Two devices with 264 nozzles each were fabricated, featuring straight and triangular nozzle configurations, both with a height of 4 µm and a minimum width of 10 µm. The devices were rendered hydrophilic via oxygen plasma treatment. A photocurable acrylate monomer served as the dispersed phase, while an aqueous polyvinyl alcohol solution acted as the continuous phase. The straight nozzles produced polydisperse droplets with diameters exceeding 30 µm and coefficient-of-variation (CV) values above 10%. In contrast, the triangular nozzles, with an opening width of 38 µm, consistently generated monodisperse droplets with diameters below 20 µm, CVs below 4%, and a maximum throughput of 0.5 mL h−1. Off-chip photopolymerization of these droplets yielded monodisperse acrylic microspheres. The low-cost, disposable, and scalable PDMS-based SE device offers significant potential for applications spanning from laboratory-scale research to industrial-scale particle manufacturing.